2022
DOI: 10.18662/brain/13.1/288
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety in Home-Quarantined Patients with COVID-19

Abstract: One of the challenges of the current pandemic in Romania has been the monitoring of COVID-19 positive patients isolated at home by their family doctors. There was no legal framework or experience in remote medical consultations and there were no clear and comprehensive guidelines for therapeutic management at the beginning of this study. As the pandemic evolved, one of the problems identified from practical experience was that anxiety in this category of patients is an underestimated factor. The present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…19,20,25,27,30,31,34,37,39,43,46,48 Only three quantitative studies reported adaptive wellbeing outcomes. 31,46,48 Reasons for self-isolation were COVID-19 infection, 21,24,26,28,29,31,33,35,37,40,41,43,45,4749 suspected infection, 42 close contact with an infected person, 30,36,39,52,54 or a combination of these. 19,20,22,23,25,27,32,34,38,44,50,51,53 One study did not report a reason.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…19,20,25,27,30,31,34,37,39,43,46,48 Only three quantitative studies reported adaptive wellbeing outcomes. 31,46,48 Reasons for self-isolation were COVID-19 infection, 21,24,26,28,29,31,33,35,37,40,41,43,45,4749 suspected infection, 42 close contact with an infected person, 30,36,39,52,54 or a combination of these. 19,20,22,23,25,27,32,34,38,44,50,51,53 One study did not report a reason.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two studies did not report lockdown context, all but one 19 related to aims 2 and 3. 21,22,24,26,28,3035,37,38,40,43,44,47,48,5254…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations